Is Scientifically Based Reading Instruction Effective for Students With Below-Average IQs?. (April 2014) - Allor, Jill H.; Mathes, Patricia G.; Roberts, J. Kyle; Cheatham, Jennifer P.; Otaiba, Stephanie Al
This longitudinal randomized-control trial investigated the effectiveness of scientifically based reading instruction for students with IQs ranging from 40 to 80, including students with intellectual disability (ID). Students were randomly assigned into treatment ( n = 76) and contrast ( n = 65) groups. Students in the treatment group received intervention instruction daily in small groups of 1 to 4 for approximately 40 to 50 min for 1 to 4 academic years. On average, students in the treatment group made significantly greater progress than students in the contrast condition on nearly all language and literacy measures. Results demonstrate the ability of students with low IQs, including students with mild to moderate ID, to learn basic reading skills when provided appropriate, comprehensive reading instruction for an extended period of time.